O instituto da quase nacionalidade e a cláusula de reciprocidade: uma perspectiva luso-brasileira de condição jurídica especial - Coelho, Everton Paul Matheus (2022)
The present work aims at the analysis of the institute of quasi-nationality, also known as Portuguese-Brazilian citizenship, from the point of view of the relationship between the Brazilian and Portuguese peoples and states. The study of the subject begins by approaching the nature of the right to nationality, its relevance to individuals and States, as well as its correlation and distinction from other concepts that permeate the fields of legal, sociological, philosophical and political research, among them, the concepts of nation, people, population, culture, territory, State, citizenship and the exercise of civil, political and social rights. Following, the systems of attribution of the right to nationality and citizenship in the Brazilian and Portuguese legal system are explored, with emphasis on their particular characteristics, their criteria for establishing a legal-political bond, primary and secondary species, the forms of loss and reacquisition, nationality and the internal reciprocity clauses between Brazil and Portugal, namely, article 12, § 1, of the Brazilian Constitution and articles 4 and 15 of the Portuguese Constitution. After examining those issues carefully, a comparative observation between the legal systems regarding originary and derived nationality, the internal and external reciprocity clauses, through the application of the Treaty of Friendship, Cooperation and Consultation, is entered. This research was based, mainly, on bibliographic sources, such as doctrinal works, scientific articles, judicial and administrative decisions, from both States and guided by theoretical issues and sensitive practices, inspired by previous interest and the author’s professional activity in the field